Metformin Inhibits NLR Family Pyrin Domain Containing 3 (NLRP)-Relevant Neuroinflammation via an Adenosine-5′-Monophosphate-Activated Protein Kinase (AMPK)-Dependent Pathway to Alleviate Early Brain Injury After Subarachnoid Hemorrhage in Mice - Jin, Lei; Jin, Fa; Guo, Shenquan; Liu, Wenchao; Wei, Boyang; Fan, Haiyan; Li, Guangxu; Zhang, Xin; Su, Shixing; Li, Ran; Fang, Dazhao; Duan, Chuanzhi; et al. (Frontiers in Pharmacology, 2022)
Neuroinflammation plays a key role in the pathogenesis of early brain injury (EBI) after subarachnoid hemorrhage (SAH). Previous studies have shown that metformin exerts anti-inflammatory effects and promotes functional recovery in various central nervous system diseases. We designed this study to investigate the effects of metformin on EBI after SAH. Our results indicate that the use of metformin alleviates the brain edema, behavioral disorders, cell apoptosis, and neuronal injury caused by SAH. The SAH-induced NLRP3-associated inflammatory response and the activation of microglia are also suppressed by metformin. However, we found that the blockade of AMPK with compound C weakened the neuroprotective effects of metformin on EBI. Collectively, our findings indicate that metformin exerts its neuroprotective effects by inhibiting neuroinflammation in an AMPK-dependent manner, by modulating the production of NLRP3-associated proinflammatory factors and the activation of microglia.